Come from away: Best practices in mini-sabbaticals for the development of young investigators: a White Paper by the SEQUIN (mini-Sabbatical Evaluation and QUality ImprovemeNt) Group. (February 2019) - Pillinger, Michael H.; Lemon, Stephenie C.; Zand, Martin S.; Foster, P. Jeffrey; Merchant, Jeanne S.; Kimberly, Robert; Allison, Jeroan; Cronstein, Bruce N.; Galeano, Claudia; Holden-Wiltse, Jeanne; Trayhan, Melissa; White, Robert J.; et al.
Abstract: Mini-sabbaticals are formal short-term training and educational experiences away from an investigator's home research unit. These may include rotations with other research units and externships at government research or regulatory agencies, industry and non-profit programs, and training and/or intensive educational programs. The National Institutes of Health have been encouraging training institutions to consider offering mini-sabbaticals, but given the newness of the concept, limited data are available to guide the implementation of mini-sabbatical programs. In this paper, we review the history of sabbaticals and mini-sabbaticals, report the results of surveys we performed to ascertain the use of mini-sabbaticals at Clinical and Translational Science Award hubs, and consider best practice recommendations for institutions seeking to establish formal mini-sabbatical programs.